OPENNESS CONCEPTION IN CHANGE OF PUBLIC ADMINISTRATION: NEW MUNICIPALITY IMPLEMENTATIONS OF MALATYA METROPOLITIAN MUNICIPALITY (Third Sector Social Economic Review, 2017)
Based on the change in public administration due to the globalization, there is a transition process from Classic Public Administration to the New Public Administration and the governance. This transition process moves from the classic solid public administration based on the concept of the secrecy and closeness to a more  flexible structure, where “openness” is foreseen as a new administration concept. In nowadays, it is understood that the administration has gone to a new understanding that implies openness in the implementations of transparency, translucence and accountability. There are mainly two purposes of this study. The first is to explain the essential concepts related to openness conception in the change of public administration; the historically development of openness conception in change of public administration from Classic Public Administration to New Public Administration and Governance perspectives; and the causes and features of openness conception. The second is to examine the new municipality implementations based on the understanding of openness in the context of ""new projects and applications"" and ""strategic plans"" of Malatya Metropolitan Municipality in 2010 and afterwards. Openness conception in the change of public administration, which constitutes the general purpose of the employee, has been discussed on the world scale and the process and reasons for change in Turkey are excluded from the study. As a narrow purpose, this study evaluates Malatya Metropolitan Municipality’s new municipality activities since 2010, based on openness conception in the annual reports and strategic plans published by the Municipality.
Keywords: Change; Change in Public Administration; Openness; Secrecy and Closeness; New Municipality Implementations of Malatya Metropolitan Municipality.